Ethylene Effects on Amylase Activity from Isolated Barley Aleurone Layers : Possible Modification by Proteolytic Enzymes - Eastwell, Kenneth C. (1982)
The effect of protease inhibitors on the response of gibberellic acid-treated barley aleurone layers to ethylene was examined. In the absence of protease inhibitors, ethylene plus gibberellic acid initially increased the production of amylase activity relative to layers incubated with gibberellic acid alone. Exposure to ethylene plus gibberellic acid for 48 hours or longer, however, led to depressed levels of amylase activity compared to samples incubated with gibberellic acid in hydrocarbon-free air. The direct assay of proteolytic activity revealed a small increase in activity in response to ethylene. The significance of this response was probed further by including inhibitors of barley proteases in the incubation medium. When potassium bromate was introduced, ethylene did not cause any alteration in amylase activity compared to samples incubated in hydrocarbon-free air. However, in the presence of N-ethylmaleimide, ethylene treatment induced a 52% increase in amylase activity recovered from samples after 48 hours. These results suggest that proteases contribute to the loss of amylase activity in response to ethylene and thus alter the apparent effect of ethylene on amylase synthesis. The effect of protease inhibitors on other hydrolases is also discussed. During the incubation period, the pH of the medium declined significantly. However, ethylene had no effect on the extent of this decline.